(untitled) (Journal of Social Sciences Review, 2023)
he present study attributed to determining the influence of organizational structure on learners’ achievement. For this purpose, a public and public-private partnership model adopted by schools was considered. A quantitative, descriptive approach was followed, and a survey technique was used. The study was delimited to Punjab province and also delimited to public elementary schools, and the PPP model adopted FAS and EVS schools. The multi-stage random sampling procedure was followed to choose the sample. The sample was comprised of 652, including 506 Heads from Public schools and 146 Heads from PPP model-adopted schools. The researchers developed a questionnaire, validated before the actual collection of data. It was concluded that different parameters of the organizational structure of both types of institutions influence learners’ achievement. A fully developed organizational structure of schools leads to better learners’ academic achievement and results in improved performance of schools. Therefore, it was recommended that efforts should be made to develop a better organizational structure.